Case Report: Atypical motor development in a patient with the mosaic form of Down syndrome and spinal muscular atrophy type 2- long-term observation - Gajewska, Ewa; Fliciński, Jędrzej; Sobieska, Magdalena; Michalska, Joanna; Żarowski, Marcin; Steinborn, Barbara (Frontiers in Genetics, 2024)
A boy is presented in whom Down Syndrome mosaicism and spinal muscular atrophy by overlapping clinical symptoms delayed the diagnosis and caused complicated motor development. The boy from the first pregnancy was delivered vaginally, week 37, Apgar 10, birth weight 3,650 g. The mother, aged 30, had no family history of Down Syndrome or neuromuscular diseases. Primary diagnosis at the age of 3 weeks: unbalanced male karyotype -mos 47, XY+21 [22]/46, XY. At 20 months, the parents observed the disappearance of the high kneeling function and asked for a neurologist’s consultation. The neurological examination showed symmetrically reduced muscle tone and symmetrically weakened knee and ankle tendon reflexes. The physiotherapeutic assessment revealed a symmetrical weakening of muscle strength and hand tremor (features characteristic of patients with spinal muscular atrophy). The final diagnosis, set at the age of 27 months, was thus the mosaic form of Down Syndrome and spinal muscular atrophy type 2.